Laws of Solon (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, Solon's laws and a little of his life in Athens are covered, and information such as the division of the population into classes is mentioned. In addition, the period of Solon's travels and poetry is also covered. mentioned.